Culture Prefigures Cognition in Pan/Homo Bonobos - Sue SAVAGE-RUMBAUGH; William M. FIELDS; Par SEGERDAHL (Theoria, 2010)
This article questions traditional approaches to the study of primate cognition. Because of a widespread assumption that cognition in non-human primates is genetically encoded, these approaches neglect how profoundly apes’ cultural rearing experiences affect test results. We describe how three advanced cognitive abilities – imitation, theory of mind and language – emerged in bonobos maturing in a Pan/Homo culture.